Epigenetics of T cell aging. Issue 4 (27th June 2018) - Goronzy, Jörg J.; Hu, Bin; Kim, Chulwoo; Jadhav, Rohit R.; Weyand, Cornelia M.
Abstract: T cells are a heterogeneous population of cells that differ in their differentiation stages. Functional states are reflected in the epigenome that confers stability in cellular identity and is therefore important for naïve as well as memory T cell function. In many cellular systems, changes in chromatin structure due to alterations in histone expression, histone modifications and DNA methylation are characteristic of the aging process and cause or at least contribute to cellular dysfunction in senescence. Here, we review the epigenetic changes in T cells that occur with age and discuss them in the context of canonical epigenetic marks in aging model systems as well as recent findings of chromatin accessibility changes in T cell differentiation. Remarkably, transcription factor networks driving T cell differentiation account for many of the age‐associated modifications in chromatin structures suggesting that loss of quiescence and activation of differentiation pathways are major components of T cell aging. Abstract : Review on aging process in T cells is characterized by changes in chromatin structures, many of which resemble epigenetic modifications seen with differentiation.